Aspectos psicosociales que influyen en la adaptación al país de tres adolescentes migrantes venezolanos a partir de sus experiencias basándose en la Teoría Ecológica de Bronfenbrenner (2022)
This research is developed from the voices of 3 adolescents and their experiences about their migration process and how they are involved in their adaptation in different environments. In this sense, knowing the stories of adolescents of Venezuelan origin, allows us to have an approach to the understanding of mimes, what they want to tell us in relation to their migratory experience, reception in Colombia and psychosocial aspects involved in its adapta tion. Given the importance of this research, it is proposed from the qualitative methodology with a phenomenological thread and from the historicalhermeneutic paradigm, where adolescents were the main participants in the research process, for data collect ion an indepth interview is implemented; through the transcription and analysis of the interviews, categories and subcategories are determined, which correspond to the adaptation, migration and theoretical approach of the postulate of Urie Bronfenbrenner, allowing the recognition of experiences, feelings, expectations and transformations that migration brings.